Impression Management of the Muslim Preacher in Indonesia - Irta Sulastri; Zaim Rais; Bukhari Bukhari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
When delivering a presentation, a person will manage the impression that others have of him. In Indonesia, Islamic preachers also tend to their beliefs. Some preachers are well-liked by the congregation because of their ability to manage their image, whereas others are disliked or despised. Syafwan Diran is one notable Preacher in Padang, and his sermons are well-received by his congregation; thus, he is frequently invited to preach at events. This research explores the impression management performed by Syafwan Diran. It is qualitative research, with data gathered through observation and in-depth interviews with the informants. The results showed that Syafwan Diran managed his impression by presenting techniques created harmoniously when appearing in front of his congregation. He also has a reasonable manner and a commitment to preaching. Therefore, his preaching is well received and eagerly anticipated by his community.